Autoantibody Specificities in Myasthenia Gravis; Implications for Improved Diagnostics and Therapeutics - Lazaridis, Konstantinos; Tzartos, Socrates J. (Frontiers in Immunology, 2020)
Myasthenia gravis (MG) is an autoimmune disease characterized by muscle weakness and fatiguability of skeletal muscles. It is an antibody-mediated disease, caused by autoantibodies targeting neuromuscular junction proteins. In the majority of patients (~85%) antibodies against the muscle acetylcholine receptor (AChR) are detected, while in 6% antibodies against the muscle-specific kinase (MuSK) are detected. In ~10% of MG patients no autoantibodies can be found with the classical diagnostics for AChR and MuSK antibodies (seronegative MG, SN-MG), making the improvement of methods for the detection of known autoantibodies or the discovery of novel antigenic targets imperative. Over the past years, using cell-based assays or improved highly sensitive immunoprecipitation assays, it has been possible to detect autoantibodies in previously SN-MG patients, including the identification of the low-density lipoprotein receptor-related protein 4 (LRP4) as a third MG autoantigen, as well as AChR and MuSK antibodies undetectable by conventional methods. Furthermore, antibodies against other extracellular or intracellular targets, such as titin, the ryanodine receptor, agrin, collagen Q, Kv1.4 potassium channels and cortactin have been found in some MG patients, which can be useful biomarkers. In addition to the improvement of diagnosis, the identification of the patients’ autoantibody specificity is important for their stratification into respective subgroups, which can differ in terms of clinical manifestations, prognosis and most importantly their response to therapies. The knowledge of the autoantibody profile of MG patients would allow for a therapeutic strategy tailored to their MG subgroup. This is becoming especially relevant as there is increasing progress towards the development of antigen-specific therapies, targeting only the specific autoantibodies or immune cells involved in the autoimmune response, such as antigen-specific immunoadsorption, which have shown promising results. We will herein review the advances made by us and others towards development of more sensitive detection methods and the identification of new antibody targets in MG, and discuss their significance in MG diagnosis and therapy. Overall, the development of novel autoantibody assays is aiding in the more accurate diagnosis and classification of MG patients, supporting the development of advanced therapeutics and ultimately the improvement of disease management and patient quality of life.